Masukan Teknologi Tinggi untuk Meningkatkan Kelas Kesesuaian Lahan kelapa Sawit (Studi Kasus PT. Teso Indah) - Besri Nasrul; Edison Anom (Universitas Riau, 2008)
Identification of high inputs to increase the land suitability for oil palm plantation was carried out at PT. Teso Indah, Indragiri Hulu, Riau in 2006. The land evaluation system applied in this study was maximum limiting factors. The result of this study indicated that reas occupied by three soil mapping units were: SPT1 of 3,988.36, SPT2 of 807.57 and SPT3 of 21.07 ha. Actual land suitability classes of PT. Tweso Indah were not suitable currently and the limiting suitability factors are depth (100-200 cm), flood, drainage, pH, and base saturation. The high inputs needed to increase the suitability class are compacted peat and draiage channel construction.